Relationship Of Children's Eating Patterns During The Covid-19 Pandemic With The Nutritional Status Of Preschool Age Children In Tugala Village, Sirombu District, West Nias Regency 2022 - Herlina (Institute of Computer Science (IOCS), 2022)
Monitoring the nutritional status of children at the West Nias Health Office is carried out twice a year in February and August. Monitoring was carried out to determine the nutritional status of children in every region in West Nias Regency and to find out some descriptions of the prevalence of children's nutritional status with several indicators. Indicators that can be used to determine the nutritional status of children in the area can be seen from indicators of children's weight according to age (W/A), indicators according to height for age (TB/U), and indicators of weight according to height (BB/TB). According to the local Health Office, the highest prevalence of malnutrition is in West Nias Regency, reaching 9.89%. From the data above, it has been shown that before the COVID-19 pandemic that occurred in the world and in Indonesia itself, nutritional problems that occurred in children were still high, especially coupled with the occurrence of cases of the spread of COVID-19 that had occurred in various countries around the world. The impact caused by the COVID-19 pandemic will be malnutrition due to various reasons, including: (1) poor diet due to declining finances, (2) non-standard nutrition, low level of hygiene, low access to health, and high spread of disease. This research is a research method approach Crossectional. The research sample is 67 people.